Selenium(IV) Derivatives of N-(o-Hydroxy Substituted Benzyl) Alanines - Shah, Ranjana; Gangwar, Tripti; Chandra, Madhup (Asian Journal of Chemistry, 2010)
Several selenium(IV) derivatives of N-(o-hydroxy substituted benzyl) alanines have been prepared by the interaction of selenium tetraisopropoxide with the latter in 1 : 1, 1 : 2, 1 : 3, 1 : 4 and 2 : 3 molar ratios in benzene medium. The various compounds thus prepared were obtained generally as coloured solids. However, amongst them those containing isopropoxy group(s) were found to be hygroscopic. All these compounds were characterized by azeotrope and elemental analysis, as well as by IR and PMR spectral measurements.